Evaluation of Usage of Drugs in Pregnancy at Private Hospitals - Patel, Shivani; Patel, Karishma; Patel, Hely; Gajjar, Utkarsh; Deshpande, Shrikalp; Mathuria, Akash (Journal of Pharmacy Practice and Community Medicine)
Background: Pregnancy represents a special physiological state during which the use of the drug is inevitable due to the risk of teratogenicity with drugs. The evaluation of prescribing drugs in pregnancy is required due to a lack of knowledge about the harmful effects of these drugs in pregnant women and fetuses. Aim: To evaluate prescribing pattern of drugs and the FDA drug risk category in pregnant women at private hospitals. Materials and Methods: The observational prospective and multicenter study were conducted in 386 pregnant women for 6 months. Each prescription was analyzed for demographic variables, medical illness, antimicrobials, risk categories of drugs prescribed, dosage forms, and WHO prescribing indicators. Results: A total of 2507 drugs were reported in the 637 prescriptions of 386 patients. A large proportion of women had anemia during pregnancy (42.9%). Majority of prescriptions prescribed oral dosage forms of drugs (81.53%) and injections (15.59%). The majority of drugs used in this study were from Category A which included anti-anemic, thyroid therapy drugs, vitamins, and minerals, followed by category C which included calcium supplements, muscle relaxants, and antihypertensive medications. No drugs were prescribed from category X. Conclusion: Iron, Calcium, and Folic acid along with Vitamins and Minerals were the most frequently prescribed drugs. In general, the drug use pattern is rational with few exceptions. The majority of drugs were used from category A followed by Category C. Drugs prescribed by their Brand name were higher than prescribed by their Generic name.
Keywords: Pregnancy; WHO prescribing indicators; FDA Drug Risk Categories; Antihypertensive medication in pregnancy; Vitamins and Minerals.